Endogenous Risk Exposure and Systemic Instability - Shu, Chong (Management Science, 2025)
Most research on systemic stability assumes an economy where banks are subject to exogenous shocks. However, in practice, banks choose their exposure to risk. I show that there exists a network risk-taking externality: the risk exposure choices made by connected banks are strategically complementary. Banks within financial networks, especially densely connected ones, become endogenously exposed to excessive risks. The theory offers several novel perspectives on policy debates. For instance, it suggests that limiting government bailouts to interbank exposures can effectively reduce endogenous systemic risk. This paper was accepted by Kay Giesecke, finance. Funding: This work was financially supported by the USC Dornsife Institute for New Economic Thinking Fellowship, the Marshall PhD Fellowship, and European Finance Association Doctoral Tutorial Best Paper Prize. Supplemental Material: The online appendix is available at https://doi.org/10.1287/mnsc.2022.01519 .